Kearifan Lokal Masyarakat Dieng dalam melestarikan Harmoni dan Budaya Ruwatan Rambut Gimbal - Rifqi Fathulhuda; Nur Aini Zakiyatin (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This research examines the local wisdom of the Dieng Highlands community through the Ruwatan Rambut Gimbal tradition as an effort to maintain harmony between humans, nature, and the spiritual dimension. The phenomenon of dreadlocks is considered a